(untitled) (Damu Journal of Sport Sciences, 2025)
Attitudes are among the main topics studied by social psychology and are learned evaluative responses to topics, events and other stimuli. When we study the attitudes of an academic scientific segment of the elite on a very important topic, which is the topic of sports, physical fitness, sports games and physical culture, knowing that we must expect that these university students have a cognitive component at least or a negative component mostly towards sports and physical fitness and their health, physical, psychological and social benefits. The research problem is limited to the fact that most private college students avoid practicing morning sports exercises or physical fitness exercises in the gym or through open playgrounds spread in most scientific or human colleges during daily attendance, and this has clearly affected their level of physical, health and psychological fitness. The aim of the research was to design a scale for the attitudes of university students in private colleges in Karbala towards sports and physical fitness and to study the attitude of private university students in Karbala towards sports and physical fitness. As for the human field, it was (500) students from private colleges in Karbala. The researcher used the descriptive method because it is the appropriate method in addressing the research problem in terms of designing the scale and using the survey method for a questionnaire. The research sample was (500) university students from scientific and human colleges of private colleges in Karbala, where the number of male students was (350) and the number of female students was (150) female university students. The researcher concluded that a standardized scale was designed for attitudes towards sports and physical fitness for students. Private colleges include (60) paragraphs (34) positive paragraphs and (26) negative paragraphs through which the attitudes of university students in private colleges towards sports and physical fitness can be diagnosed. The degree of the scale of students' attitudes towards sports and physical fitness in the private colleges included in the examination appeared at (189.8), which represents a moderate attitude towards sports and physical fitness by the examined research sample.